Determinants of climate-smart agriculture technology adoption among smallholder rice farmers in Gwagwalada Area Council, Federal Capital Territory, Nigeria - Olohungbebe, S. A.; Bako, J. O.; Olutola, J. T. (ADAN JOURNAL OF AGRICULTURE, 2025)
Small-scale rice farmers face significant farming challenges posed by climate change, particularly in Nigeria where the major source of their livelihood is agriculture. This study examined the determinants of climate smart agricultural (CSA) technologies adoption among small-scale rice farmers in Gwagwalada Area Council, Federal Capital Territory, Nigeria. The specific objectives of the study were to describe the socioeconomic characteristics of small-scale rice farmers, evaluate the various climate smart agricultural (CSA) technologies adopted by small-scale rice farmers, analyze the factors influencing the adoption of climate smart agricultural (CSA) technologies among small-scale rice farmers and describe the constraints faced by small-scale rice farmers in the adoption of climate agricultural (CSA) technologies. A wellstructured questionnaire was used to gather data from 80 small-scale rice farmers. The data were analyzed using descriptive statistics and probit regression model. The results revealed that conversational agricultural practices and mixed cropping had mean values of 3.21 and 3.61 respectively and were the most widely adopted climate smart agricultural (CSA) technology used, while drought resistant varieties had a low mean of 2.37. Experience in farming positively influenced CSA adoption (p<0.05), whereas larger farm negatively influenced CSA adoption (p<0.01). The constraints they faced include poor infrastructure, lack of credit facilities, inadequate extension services and limited awareness. The study highlights the urgent implementation for some targeted intervention such as improved access to extension services, credit and infrastructural development which will greatly enhance the adoption of CSA technologies.